2005
DOI: 10.1111/j.0022-202x.2004.23518.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinin B2 Receptor-Coupled Signal Transduction in Human Cultured Keratinocytes

Abstract: Kinins are key pro-inflammatory peptides that exhibit mitogenic effects in tissue-specific cellular systems. Since the life span of the keratinocyte is regulated by receptors that control proliferation and differentiation, and since both processes are affected during wound healing, we have examined the consequence of kinin B2 receptors (B2R) activation in cultured human keratinocytes. Stimulation of keratinocytes by Lys-bradykinin (LBK) induced a rapid and sustained phosphorylation of 42/44 mitogen-activated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
(39 reference statements)
3
19
0
Order By: Relevance
“…This result is in agreement with the finding that a tyrosine kinase inhibitor blocked the effect of BK in MDCK cells (Xing et al, 1997). However, we cannot rule out the possibility that BK induces the phosphorylation of other proteins, since BK induces the phosphorylation of p44/42 MAPKs and src in keratinocytes (Vidal et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with the finding that a tyrosine kinase inhibitor blocked the effect of BK in MDCK cells (Xing et al, 1997). However, we cannot rule out the possibility that BK induces the phosphorylation of other proteins, since BK induces the phosphorylation of p44/42 MAPKs and src in keratinocytes (Vidal et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported that kinins may increase DNA synthesis and cell division in several cellular systems [26]. Nevertheless, some data are contradictory and state that kinins do not stimulate keratinocyte proliferation [27][28][29] or induce a weak response when compared with that produced by epidermal growth factor (EGF) [30]. These previously mentioned works were performed in vitro and some used epidermal scales of psoriatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bound antibodies were detected using a chemiluminescence kit (Pierce, USA). The antibodies used for the first immunodetection were stripped as previously described [15] and total amount of ERK1/2 present in each sample was assessed using a polyclonal antibody (Cell Signaling). Specificity was evaluated by pre-incubating cells for 30 min with an excess of a B 1 R (des-[Arg 9 ]-Leu 8 -BK or Lys-des-[Arg 9 ]-Leu 8 -BK, Bachem), or a B 2 R antagonists before stimulation.…”
Section: Cell Culture and Western Blottingmentioning
confidence: 99%